Finland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Finland has undergone a fundamental structural shift from a resource-based to a knowledge-based economy. The productivity surge in the dynamic information and communications technology sector fueled a strong export-driven recovery. However, the optimism of the past year has dissipated, as the global slowdown takes its toll especially on the high-tech sector, including international market leaders such as Nokia. This paper assesses the services sector and its potential for employment creation, in particular in the area of personal services and other services with low skill requirements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet